The impact of SFAS 157 on fair value accounting and future bank performance - Ehalaiye D; Tippett M; van Zijl T (Emerald Publishing Limited)
Purpose The purpose of this paper is to investigate whether levels-classified fair values of US banks based on SFAS 157: Fair Value Measurements, as recognised in the quarterly financial statements of the banks over the period from 2008 until 2015, have predictive value in relation to the banks’ future financial performance measured by operating cash flows and earnings over a three-quarter horizon period. In addition, we consider whether the global financial crisis (GFC) impacted the relationship between SFAS 157–based levels‐classified fair values and bank future financial performance. Design/methodology/approach We develop hypotheses connecting the net levels-classified bank fair values based on SFAS 157 with banks’ future financial performance. We test the hypotheses by estimating three-period quarters’ ahead forecasting models. We also use these models to test for the impact of the GFC on the relationship between the fair values and future financial performance. Findings Our findings suggest that the levels-classified net fair values based on SFAS 157 have predictive value in relation to future cash flows for banks. There is significant variation, across the levels, in the predictive value of levels-classified net fair values for future performance. Our findings indicate that the GFC has limited impact on the predictive value for cash flows, but the GFC had a significant adverse impact on earnings, and, with allowance for the effect of the GFC, the Level 2 net fair values have predictive value for the future earnings. Originality/value The study provides the first direct empirical evidence on the relationship between the SFAS 157 levels-classified quarterly bank fair values recognised in publicly available financial statements and banks’ future performance. Our results are consistent with the findings from earlier research (Ehalaiye et al., 2017) using annual data disclosed in the supplementary notes to the financial statements of US banks based on SFAS 107. The study, makes a significant contribution to the question of frequency of reporting and to the disclosure vs recognition debate. The study has implications for policy makers, regulators and accounting standards setters such as the Securities and Exchange Commission and the Financial Accounting Standards Board in evaluating the use of fair value measurement in financial reporting.
Keywords: Fair value accounting; Operating cash flows; Operating earnings; Predictive value; SFAS 157; 0806 Information Systems; 1501 Accounting, Auditing and Accountability; 1502 Banking, Finance and Investment